Application of tofuwaste bioactivation in making organic liquid fertilizer from market waste and dry leaves - Hernowo Widodo; Laras Andria Wardani; Vicky Anderesta Kuswoyo (Universitas Darussalam Gontor, 2021)
Organic fertilizers contain a lot of residual organic matter that has been decomposed and is ready for consumption by plants. The raw materials for organic liquid fertilizer used in this study were market waste, dry leaves, and the addition of three bio activators (tofu wastewater, Stardec, and EM4). The selection of tofu liquid waste is done because it is easy to obtain, cheap, and reduces environmental pollution. Therefore, the purpose of this study was to analyze the quality and quality of the manufacture of liquid fertilizer using the tofu industry's liquid waste bio activator compared to other bio activators. The method used in this research is the experimental manufacture of liquid fertilizer with anaerobic fermentation, which is then applied to the growth of kale. The results of this study are the quality and quality of the manufacture of liquid fertilizer using a liquid waste bio activator tofu industry is quite good, although it still does not meet the minimum Technical Requirements for Organic Fertilizer standards issued by the Decree of the Minister of Agriculture of the Republic of Indonesia Number 261/KPTS/SR.310/M /4/2019. This can be seen from the average height of the kale plant which is not much different from the use of popular bio activators on the market (EM4 and Stardec), where the average height yield is 6.72 cm on the seventh day